The effective and proper exercise of appraisal rights under the South African Companies Act, 2008 : developing a strategic approach through a study of comparable foreign law - Yeats, Jacqueline (Department of Commercial Law, 2016)
This thesis seeks to identify how the appraisal rights remedy, which was introduced into South African company law for the first time by section 164 of the Companies Act 71 of 2008 ('the South African Act'), should be interpreted and applied in order to facilitate its effective and proper exercise. When the draft version of the South African Act was initially published for public comment, critics raised concerns that the inclusion of the appraisal remedy was undesirable and unnecessary. These concerns were largely motivated by the fact that at the time appraisal rights were a novel concept and thus a completely unknown quantity in South African law. As a result there was much uncertainty in the legal and commercial sector as to how these rights would be interpreted, how they would function and how frequently they would be used. However, since the commencement date of the South African Act (being 1 May 2011) to date no appraisal rights matter has come before our courts and it could therefore be argued that the initial concerns of the critics regarding the impact that the inclusion of appraisal rights would have on South African company law were unfounded. This 'lack of use' phenomenon is in line with the general trend experienced in foreign jurisdictions where the appraisal remedy has been on the statute books for decades, such as the United States of America ('USA' or 'US'), Canada and New Zealand. Due to the fact that appraisal rights are notoriously underutilised they have often been dismissed as an ineffective remedy for minority shareholders. Clearly it could not have been the intention of the drafters of the South African Act to include an ineffective or useless remedy. My research indicates that the lack of use of the appraisal remedy in comparable jurisdictions is due to a number of factors but can be broadly attributed to the complexity, uncertainty and expense associated with the exercise of appraisal rights. The thesis therefore seeks to identify the various causes of the lack of effectiveness apparent in the USA, Canada and New Zealand, to examine the relevance of these in the South African context and to consider possible ways of addressing these challenges. The ultimate objective of the thesis is to devise measures which may be taken so that the appraisal remedy can function more effectively, or at least as effectively as possible, in South Africa.